Strategi Retensi Generasi Z melalui Literasi Digital dan Kepemimpinan Adaptif: Studi pada UMKM Banyuwangi - Ni Kadek Yuliandari; Kurnia Riesty Utami; Moh. Fahrurrozi; Luh Kartika Ningsih (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2026)
Digital transformation and workforce demographic changes have created new challenges in human resource management, particularly regarding the retention of Generation Z in the Micro, Small, and Medium Enterprises (MSMEs) sector. Generation Z, as digital natives, possesses advantages in utilizing technology; however, they often encounter obstacles such as limited formal training, inadequate digital infrastructure, and high expectations for leadership styles. This study aims to explore the role of digital literacy and adaptive leadership in sustaining Generation Z retention within MSMEs in Banyuwangi. The research employed a qualitative descriptive approach with a purposive sampling technique involving 30 informants, consisting of Generation Z employees (aged 18–29 years) and MSME owners in the culinary, handicraft, and service sectors. Data were collected through in-depth interviews, participatory observations, focus group discussions, and secondary document analysis, and then analyzed using thematic analysis with source and method triangulation to ensure data credibility. The findings identified four main themes: (1) digital literacy of Generation Z, (2) adaptive leadership styles, (3) dynamics of Generation Z retention, and (4) the integration of digital literacy and adaptive leadership as a retention strategy. The results indicate that digital literacy enhances Gen Z’s contribution to digital marketing and e-commerce, while adaptive leadership characterized by flexibility and support strengthens their organizational loyalty. The integration of these two aspects produces a contextual retention strategy that can reduce turnover risks and improve MSME competitiveness.